The relationship between environmental sanitation and nutritional status with soil-transmitted helminths infection in elementary school children - Maksum, Tri Septian; Mokodompis, Yasir; Ali, Indra Haryanto; Nurfadillah, Ayu Rofia (Universitas Wiralodra, 2023)
Soil-Transmitted Helminths (STH) infection is still a significant public health problem worldwide, including in Indonesia. This infection is caused by worms whose life cycle requires a soil medium in the maturation of eggs or larvae into an infective form and mainly occurs in children of primary school age. Poor environmental sanitation and malnutrition are the leading causes of STH infection. This study aims to determine the relationship between ecological sanitation, nutritional status, and STH infection incidence in elementary school children. This type of research is descriptive research. The research location is SDN 22 Telaga Biru, Telaga Biru District, Gorontalo Regency. The sample was 32 SDN 22 Telaga Biru students, obtained using the total sampling technique. Data was collected using questionnaire instruments, Body Mass Index (BMI) examinations, and fecal examinations at the UPTD Regional Health Laboratory Center of Gorontalo Province. The data were further analyzed univariately. The results showed that most environmental sanitation conditions did not qualify, such as latrine conditions (68.8%), SPAL conditions (75.0%), trash can conditions (87.5%), and clean water facilities (68.8%). Nutritional status (BMI/U) was most in the normal category (65.6%), and no helminth eggs were found in respondents (negative STH), so a relationship analysis could not be carried out. It is suggested that the school and parents support government programs related to providing mass worm-prevention drugs.